Counting of fungi and detection of mycotoxins in feed supplies and balanced feeds in pig farms in the province of Coronel Portillo, Ucayali, Peru - Huatuco C., David (2023)
The aim of this study was to perform a fungal count and detect mycotoxins in feed supplies and balanced feed from pig farms in four districts of Coronel Portillo, Ucayali. Fifty samples were collected (35 of balances feeds [three rearing stages] from 20 farms and 15 of feed supplies from 10 of these farms). The fungal count was performed using the plate count method and the detection of mycotoxins (aflatoxin B1, ochratoxin A and zearalenone) using commercial ELISA kits. Results showed that 50% of farms had at least one sample of unacceptable quality. Likewise, 6/15 (40%) and 5/35 (14.3%) of feed supplies and balanced feed samples, respectively, had unacceptable quality. The starter feed had the highest average fungal count (9.6 x 104 CFU/g). There was an association between quality and type of food, but none between quality and origin. Half of the farms had at least one feed sample with mycotoxins above the Maximum Permissible Level (MPL) and 42.9% (15/35) of the samples had at least one mycotoxin above the MPL. The highest mean for aflatoxin B1 was found in the starter feed (26.2 ppb) and the highest for zearalenone in breeders feed (74.5 ppb).